Design of a Multiple-Input SC DC-DC Converter Realizing Long Battery Runtime - Kei EGUCHI; Sawai PONGSWATD; Amphawan JULSEREEWONG; Kitti TIRASESTH; Hirofumi SASAKI; Takahiro INOUE (My University, 2010)
A multiple-input switched-capacitor DC-DC converter which can realize long battery runtime is proposed in this letter. Unlike conventional converters for a back-lighting application, the proposed converter drives some LEDs by converting energy from solar cells. Furthermore, the proposed converter can charge a lithium battery when an output load is light. The validity of circuit design is confirmed by theoretical analyses, simulations, and experiments.
Keywords: Switched capacitor; Advanced DC-DC Converters